GEOCHEMISTRYOF BEACH SANDS FROM ABU DHABI, UNITED ARAB EMIRATES (UAE) - Al Rashedi, Saeed; Siad, Abdi (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Fifty-seven beach sediment samples were collected along the beaches of Abu Dhabi, United Arab Emirates to determine their geochemical composition using X-ray fluorescence and ICP analysis. Two dominant sediments groups i.e. marine biogenic carbonate and terrigenous sediments were identified through major elements scatterplots and ternary diagram of the dominant major elements. CaO has shown negative correlation with all major and most of the trace elements with exception Sr, As and U. The scatter plots for both Al2O3 and SiO2 show positive correlation with all major elements with the exception of CaO and LOI and all the trace elements with exception of Sr,As and U. Therefore, strontium, uranium and arsenic are considered to have marine origin.